Case report: TP53 heterogeneous alteration in grade 3 type I gastric NET: a case implicating primary tumor progression - Li, Yan; Bai, Yuekui; Ti, Hongjuan; Zhou, Chunyu; Liu, Qian; Dong, Ying (Frontiers in Oncology, 2025)
Grade 3(G3) type I gastric neuroendocrine tumors (NETs) are rare, with only three documented cases in the literature to our knowledge. The case we report involves a type I gastric NET(g-NET) classified as G3, which exhibits heterogeneity in TP53 gene mutations. This suggests that G3 g-NETs may develop from G2 forms. In this tumor located in the gastric body, both G2 and G3 components coexist. The G2 component is found in the superficial mucosa and submucosa, while the G3 component is in the submucosa and muscularis propria. Genetic testing reveals that the TP53 gene is mutated in the G3 component. The coexistence of these alterations within a single primary tumor is extremely rare, indicating that the TP53 gene plays a crucial role in the progression from G2 NET to G3 NET. This case may challenge our previous understanding of g-NETs.